Evaluation of participation in public consultations carried out within the CONCISE project - Kretek-Kamińska, Agnieszka (Science Communication in Poland. Participation. Dialogue. Trust, 2021)
A direct and obvious consequence of the transformations taking place within the goals and objectives of scientific knowledge are the transformations in how it is produced. The growing importance of practical aspects of science results is, among other things, increasing the scope of participation of its potential recipients in research processes. It is intended to generate the most complete and appropriate interpretations of the researched issues, taking into account their contextual background and enabling the design of relevant actions. At the same time, it should create a basis of legitimacy for implementing the developed projects while fulfilling educational and emancipatory functions for their participants. The realization of these assumptions in a specific research process involves the development and application of appropriate methods of data collection and analysis, as well as continuous and reflective monitoring of its course, taking into account the viewpoints of all participants.This chapter presents the results of an evaluation study of public consultations on the acquisition and perception of scientific knowledge, carried out within the CONCISE project. Particular attention was paid to the issue of the participation of the actors involved in the process. The extent to which group discussion principles were implemented, the level of interest in the subject of the consultation, and involvement in the discussion were evaluated. Additionally, opinions on the organization of the meeting and the adequacy of the consultation formula for gathering opinions on the ways of communicating scientific knowledge were examined.